Diet of Nestling Spectacled Tyrants (Hymenops perspicillatus) in the Southeast Pampas Region, Argentina - Pretelli, Matías Guillermo (2014)
We studied the diet of nestling Spectacled Tyrants (Hymenops perspicillatus) in the southeast Pampas region, Argentina. From November 2012 to January 2013, we used video footage to determine prey items that the parents fed to their chicks. We obtained 54 hrs of recording time to survey 18 nests. We identified a total of 125 prey items, representing 33 different taxa, grouped into four classes: Insecta, Arachnida, Chilopoda, and Amphibia. Insects accounted for 94% of total prey. The most frequent prey items were orthopterans (Caelifera), unidentified lepidopteran larvae, and odonats (Zygoptera). Lepidopterans were numerically the most important prey item in November, odonats in December, and orthopterans in January. Diet of the nestling birds was generalist in terms of the consumption of insects, and the changes in prey consumption during the course of the breeding season support an opportunistic feeding behavior by Spectacled Tyrants.